Management of First Branchial Cleft Anomalies via a Cartilage‐Splitting Technique. (24th March 2015) - Schmidt, Richard; Conrad, David; Field, Erin; O'Reilly, Robert
Abstract : First branchial cleft anomalies are uncommon lesions that often present as periauricular infections. They have high recurrence rates, due in part to scarring secondary to prior infections and their management. These lesions have a close relationship with the facial nerve, and most authors recommend its identification and dissection because of this relationship. Nonetheless, facial nerve palsy has been reported in up to 15% of cases. We describe a novel technique for the management of first branchial cleft anomalies. Such lesions that presented in an infra‐ or postauricular location were approached via an incision through the cartilage of the pinna, between the tragus and antitragus. This technique affords direct access to the lesion without the need for facial nerve dissection. Six patients were treated. Five had prior surgery, including 3 with previous attempts at excision. There were no complications. The median follow‐up was 35 months. One patient developed a recurrence.